Pendampingan Pembaruan Packaging dan Optimalisasi Branding UMKM Masyarakat di Kelurahan Kepatihan, Kecamatan Kaliwates, Kabupaten Jember - Ajeng Khusnul Samudra Pertiwi; Moh Khoiril Mustofa; Nida Kamila Hanifah Bastian; Cahyaningtyas Tetta Riandy; Novia Nur Chasanah; Putri Aulia Nadiyatul Jannah; Grace Winata; Daud Angga Yudha; Adam Naufalianto; Shavira Yuansa; Afifah Balqis Iftinan; Agung Rhaka Oktavianto; Hesti Ayu Verawati; Laili Rohmah Romadhoni; Sefi Ika Candra; Nurshadrina Kartika Sari (Universitas Maritim AMNI Semarang, 2023)
Collaborative KKN is a service activity by students consisting of several universities. Our KKN location is in Kepatihan Village, Kaliwates District, Jember Regency. The main work program carried out by KKN Collaboration 229 students is to help Kepatihan Village MSMEs in the field of packaging and branding. Through the PANACOTTA work program, the KKN 229 group carries the theme of entrepreneurial development, entitled